2019
DOI: 10.1021/acsanm.9b01216
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Effects on the Oxygen Reduction Reaction and Irreversible Surface Oxidation of Metallic Ru Nanosheets and Nanoparticles

Abstract: Nanosheets have attracted increasing attention owing to their electrochemical properties. While the relationship between the activity and stability of metal nanoparticles has been widely reported, the activity−stability relationship of metallic nanosheets has not been characterized. Herein, we report on this relationship for Ru nanosheets and discuss its difference with the relationship for Ru nanoparticles. The oxygen reduction reaction activity of the Ru nanosheets was 130% higher than that of the nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In addition, improved stability of Pt catalysts has been reported for morphology-controlled catalysts 39 , 40 . Although most studies did not discuss the mechanism of the improved stability, we have recently reported the mechanism of the high oxidation tolerance of Ru NSs 29 . Based on the combination of in situ XAS measurements and XANES spectral simulations, the CN ave. of the Ru atoms on the surface of the nanosheet was found to be larger than that on the surface of the nanoparticle; thus, the Ru NSs showed higher oxidation tolerance.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, improved stability of Pt catalysts has been reported for morphology-controlled catalysts 39 , 40 . Although most studies did not discuss the mechanism of the improved stability, we have recently reported the mechanism of the high oxidation tolerance of Ru NSs 29 . Based on the combination of in situ XAS measurements and XANES spectral simulations, the CN ave. of the Ru atoms on the surface of the nanosheet was found to be larger than that on the surface of the nanoparticle; thus, the Ru NSs showed higher oxidation tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…The sample was immersed in a methanol/water solution to improve the wettability of the hydrophobic catalyst layer. A polychlorotrifluoroethylene-based in situ electrochemical cell was used for the in situ XAS analysis, as described in previous studies 29 , 45 . Pt wire and a RHE were used as the counter and reference electrodes, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Takimoto and Fukuda obtained Ru nanosheets by reducing RuO 2 , but their reduction methods slightly differed. Takimoto et al 73 prepared ultrathin nanosheets containing only two atomic layers by electrochemical reduction, obtaining nanosheets with a thickness of 0.6 nm (Fig. 10g and h).…”
Section: Ru Ultrathin Nanosheetsmentioning
confidence: 99%
“…Fig. 10 (a) TEM, (b) HRTEM, and (c) AFM images of Ru nanosheets; (d-f) TEM images of the intermediate products obtained at 1 h, 3 h, and 10 h, respectively; 72 (g) TEM and (h) AFM images of Ru nanosheets;73 (i) AFM image of Ru nanosheets 74. …”
mentioning
confidence: 99%